Playing it safe? Solitary vervet monkeys (Chlorocebus pygerythrus) choose high‐quality foods more than those in competition. Issue 7 (13th June 2019) - Kumpan, L. Tamara; Rothman, Jessica M.; Chapman, Colin A.; Teichroeb, Julie A.
Abstract: An important goal in foraging ecology is to determine how biotic and abiotic variables impact the foraging decisions of wild animals and how they move throughout their multidimensional landscape. However, the interaction of food quality and feeding competition on foraging decisions is largely unknown. Here we examine the importance of food quality in a patch on the foraging decisions of wild vervet monkeys ( Chlorocebus pygerythrus ) at Lake Nabugabo, Uganda using a multidestination platform array. The overall nutritional composition of the vervet diet was assessed and found to be low in sodium and lipids, thus we conducted a series of experimental manipulations in which the array was varied in salt and oil content. Although vervets prioritized platforms containing key nutrients (i.e., sodium and lipids) overall, we found that solitary vervets prioritized nutrient‐dense platforms more strongly than competing vervets. This finding was opposite to those in a similar experiment that manipulated food site quantity, suggesting that large, salient rewards may be worth competing over but slight differences in nutritional density may be only chosen when there are no potentially negative social consequences (i.e., aggression received). We also found that vervets chose platforms baited with oil‐only, and oil combined with salt, but not salt‐only, suggesting that energy was an important factor in food choice. Our findings demonstrate that when wild vervets detect differences in feeding patches that reflect nutritional composition, they factor these differences into their navigational and foraging decisions. In addition, our findings suggest that these nutritional differences may be considered alongside social variables, ultimately leading to the complex strategies we observed in this study. Abstract : Percentage of First Visits to a single Nutrient‐Dense Site in a Pentagon Array. Research Highlights: We found that vervets chose nutrient‐dense patches overall, but solitary vervets prioritized nutrient‐dense patches more heavily than competing vervets. Our results suggest that the strategies animals use to consume nutrients varies in social and asocial conditions.